2011
DOI: 10.1108/15265941111112811
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macroeconomic indicators on Indian capital markets

Abstract: Purpose -The purpose of this paper is to examine the long-run relationship between the Indian capital markets and key macroeconomic variables such as interest rates, inflation rate, exchange rates and gross domestic savings (GDS) of Indian economy. Design/methodology/approach -Quarterly time series data spanning the period from January 1995 to December 2008 has been used. The unit root test, the co-integration test and error correction mechanism (ECM) have been applied to derive the long run and short-term sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 17 publications
10
54
1
6
Order By: Relevance
“…The industrial production though small portion of Gross Domestic Product indicates the real activity in the country. On the contrary, inflation is negatively associated to the stock market returns (Pal and Mittal, 2011) 13 . Pakistan is a consumption oriented society and people do not go for the investment in the stocks.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The industrial production though small portion of Gross Domestic Product indicates the real activity in the country. On the contrary, inflation is negatively associated to the stock market returns (Pal and Mittal, 2011) 13 . Pakistan is a consumption oriented society and people do not go for the investment in the stocks.…”
Section: Discussionmentioning
confidence: 91%
“…The real income level, saving rate, financial intermediary development, and stock market liquidity proved to be significantly affecting the stock market development, while macroeconomic stability does not prove significant. Pal and Mittal (2011) examined the long term relationship between key macroeconomic variables and the Indian capital markets. They attempted to explore how Indian stock market reacts to different macroeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Indian market, a long-run positive relationship between stock prices and money supply and industrial production and a negative relation for inflation has been widely documented (Naik & Padhi, 2012;Kumar, 2013;Patel, 2012;Pal & Mittal, 2011;Aurangzeb, 2012). Benakovic and Posedel (2010) finds a positive relation between stock returns and the market index, interest rates, industrial production and oil influence, with inflation showing a negative relation for the Croatian Market.…”
Section: The Market Factormentioning
confidence: 99%
“…Wenjen Hsieh [27] examined the impact of macroeconomic factors on New Zealand stock market using GARCH model and found that New Zealand stock market positively respond to real GDP and world stock market index. Although some researchers like Pethe and Karnik [28], Bhattacharya and Mukherjee [29], Ahmed [30], Srivastava [25] and Pal and Mittal [31] attempted to identify economic factors affecting stock market in India but none of these are conclusive. In Indian contest negligible amount of research has been done for identifying systematic risk factors for Indian stock markets.…”
Section: Review Of Literaturementioning
confidence: 99%